Working Time Reduction and Employment in a Finite World - Jean-François Fagnart; Marc Germain; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the consequences of a working time reduction (WTR hereafter) in a growth model with efficiency wages and an essential natural resource (natural capital). Considering that technical progress cannot reduce the resource content of final production to zero, we show that the effects of a WTR on (un)employment depend on the abundance of natural capital. If it is unlimited, the economy converges toward a balanced growth path and a WTR lowers output, employment and wage levels along this path. With finite natural capital, the economy converges toward a stationary state. A WTR then increases the hourly wage and employment if natural capital is scarce enough, which is necessarily the case if technical progress on produced capital and labour is unbounded. The long-term elasticity of employment (resp., of the hourly wage) to the cut in hours is larger (resp., smaller) when natural capital is scarcer. A numerical analysis of the transitory impacts of a WTR confirms that when natural capital is scarcer, it increases employment more and the hourly wage less, with a less negative initial impact on output.
Keywords: J68; O44; Q57; 330; unemployment; fair wage; work sharing; (limits to) growth; natural capital